2011
DOI: 10.1007/s00114-011-0848-2
|View full text |Cite
|
Sign up to set email alerts
|

Promiscuity in mice is associated with increased vaginal bacterial diversity

Abstract: Differences in the number of sexual partners (i.e., mating system) have the potential to exert a strong influence on the bacterial communities present in reproductive structures like the vagina. Because this structure serves as a conduit for gametes, bacteria present there may have a pronounced, direct effect on host reproductive success. As a first step towards the identification of the relationship between sexual behavior and potentially pathogenic bacterial communities inhabiting vital reproductive structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 88 publications
3
21
0
Order By: Relevance
“…We found that more promiscuous primate species showed greater microbial diversity, which is consistent with microbial analyses in mice (MacManes, 2011). Promiscuity is likely to be a driving factor leading to systemic differences in the primate immune system (Nunn et al, 2000), as well as the rate of molecular evolution of genes impacting immune function (Wlasiuk and Nachman, 2010).…”
Section: Discussionsupporting
confidence: 82%
“…We found that more promiscuous primate species showed greater microbial diversity, which is consistent with microbial analyses in mice (MacManes, 2011). Promiscuity is likely to be a driving factor leading to systemic differences in the primate immune system (Nunn et al, 2000), as well as the rate of molecular evolution of genes impacting immune function (Wlasiuk and Nachman, 2010).…”
Section: Discussionsupporting
confidence: 82%
“…These factors may influence patterns of microbiota in species with pronounced sexual swellings such as chimpanzees and baboons. Paralleling established correlates of multimale mating, such as testes size and number of mates (Short, 1979;Harcourt et al, 1981;Kappeler and van Schaik, 1999;Nunn et al, 2000Nunn et al, , 2003Nunn et al, 2004), more promiscuous host species may show greater microbial diversity than less promiscuous species, consistent with recent analyses of mice (MacManes, 2011).…”
Section: Microbial Variation Among Nhpssupporting
confidence: 75%
“…STI prevalence among human populations is associated with higher levels of promiscuity [8], confirming the expected association between sexual behavior and infection rates. Promiscuity also impacts the overall community composition of the vaginal microbiome, increasing diversity in polygamous lizards [9], primates [10], and mice [11]. Mating multiply thus appears to lead to a greater sampling of the available microbial diversity within populations.…”
Section: Beneficial Stis and Sexual Selectionmentioning
confidence: 99%